(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to update Ireland’s National Physical Activity (PA) Guidelines, last published in 2009. This involved adapting the World Health Organization’s (WHO) 2020 Guidelines on PA and Sedentary Behaviour to align with the Irish context. A key innovation of this research was the development of tailored PA messages for both public and professional audiences. Methods: The project followed a three-stage process. First, a review of literature published since the evidence review for the WHO 2020 guidelines was conducted to identify any new evidence. Second, draft guidelines and accompanying messages were developed. Third, public and professional perceptions were gathered through online surveys (n = 215 public; n = 187 professionals) and a national consensus meeting with stakeholders involved in PA promotion. The surveys assessed clarity, relevance, and motivational appeal of the guidelines and messages on a 5-point Likert scale. Results: The evidence review found no substantial updates that would warrant changes to the WHO 2020 recommendations, except for children with disabilities where it was recognised that for certain disabilities a reduced level of PA may be adequate for health benefits. Survey responses indicated strong agreement among the public that the lay guidelines were clear (>3.3 on 5-point scale) for all subgroups except children aged 1–4 years and children living with disability. There was consensus that the lay guidelines were relevant (>3.0) for all groups except children living with disability. Professionals reported frequent use of such guidelines in their work (43%) and affirmed their clarity and importance (90%). The consensus meeting provided critical feedback on message framing, intensity descriptors, and content for specific subgroups, particularly children with disabilities. This collaborative process informed the finalisation of the guidelines and messages. Conclusion: The updated Irish guidelines are an adapted version of the WHO 2020 recommendations, enhanced with lay-friendly formats and persuasive messages tailored to diverse audiences. This work contributes to public health practice by providing accessible, evidence-informed guidance and public-facing messages to support PA promotion across the lifespan. Future efforts should focus on implementing a comprehensive dissemination strategy to maximise the reach and impact of these guidelines throughout Ireland. Support/Funding Source: Health Service Executive, Ireland.